La pronuncia italiana per i giovani apprendenti sloveni: che cosa ne dicono i dizionari? - Grošelj, Robert (Studia Romanica Posnaniensia, 2020)
The article deals with the representation of Italian pronunciation in five contemporary dictionaries for young Slovenian learners. As the use of a dictionary not only stimulates the development of lexical competence, but can also serve as a useful means for pronunciation learning, the article investigates five categories representing phonetic-phonological features in a dictionary: introduction to phonetics/phonology (e.g. a pronunciation guide), phonetic transcription, phonemes, consonant length and accent. The representation of these features in a dictionary for young learners should be clear and coherent, and in some cases a dictionary (especially a dictionary intended for the youngest users) should also feature audio pronunciations. The five dictionaries analysed are fragmentary with regard to the pronunciation: only one dictionary includes audio recordings (although the relation between the spelling and the pronunciation remains unclear, as it does not include a pronunciation guide); two dictionaries include deficient phonological transcriptions and incomplete pronunciation guides; one dictionary contains only the Italian alphabet with corresponding phonemes, while another dictionary is without any elements that could familiarize a Slovenian learner with Italian pronunciation.